Coping with Library Anxiety Using Interactive Technology - Ida Fajar Priyanto (Pustabiblia: Journal of Library and Information Science, 2017)
A library has been viewed as a place for learning outside of the classroom. The information technology that has resulted in digital library does not replace a library as a place. It enhances the library’s role as a learning place. However, students often experience what is called as “library anxiety” when visiting a library, especially when they visit it for the first time. Adding more technological applications will make current users get better information. And it will also help cope with any library anxiety.